Improving farmer trust and seller reciprocity in agricultural input markets: A lab-in-the-field experiment in Bangladesh - de Brauw, Alan; Kramer, Berber (2018)
Improving the quality of agricultural inputs used by farmers is a potentially important instrument to improve productivity and food security. However, most inputs are experience goods, meaning that quality is unobservable to buyers before purchase, and sellers need to use price or reputation to signal quality. Through a lab-in-the-field experiment with input retailers (sellers) and farmers (buyers) in Bangladesh, we test to what extent sellers can signal quality through prices and reputation, and whether a buyer-driven accreditation and loyalty reward scheme helps improve market outcomes. We create competitive input markets in which sellers set prices and quality, while buyers observe price but not quality when choosing their sellers. We find that sellers provide mostly low-quality products and buyers reveal low demand for more expensive, high-quality inputs. Accrediting sellers based on buyer satisfaction leads to higher input quality and more repeat purchases only when combined with loyalty rewards for accredited sellers of the high-quality product, or for their buyers. The scheme improves average earnings for sellers but not for buyers because the performance of quality signals remains weak. Thus, although small incentives may be particularly effective at improving market outcomes, they do not necessarily enhance quality signals and farmer welfare.